Effect of Mas‐related gene (Mrg) receptors on hyperalgesia in rats with CFA‐induced inflammation via direct and indirect mechanisms. (15th October 2013) - Jiang, Jianping; Wang, Dongmei; Zhou, Xiaolong; Huo, Yuping; Chen, Tingjun; Hu, Fenjuan; Quirion, Rémi; Hong, Yanguo
<x xml:space="preserve">Abstract</x> Background and Purpose Mas oncogene‐related gene (Mrg) receptors are exclusively distributed in small‐sized neurons in trigeminal and dorsal root ganglia (DRG). We investigated the effects of MrgC receptor activation on inflammatory hyperalgesia and its mechanisms. Experimental Approach A selective MrgC receptor agonist, bovine adrenal medulla peptide 8‐22 (BAM8‐22) or melanocyte‐stimulating hormone (MSH) or the μ‐opioid receptor (MOR) antagonist CTAP was administered intrathecally (i.t.) in rats injected with complete Freund's adjuvant (CFA) in one hindpaw. Thermal and mechanical nociceptive responses were assessed. Neurochemicals were measured by immunocytochemistry, Western blot, ELISA and RT‐PCR. Key Results CFA injection increased mRNA for MrgC receptors in lumbar DRG. BAM8‐22 or MSH, given i.t., generated instant short and delayed long‐lasting attenuations of CFA‐induced thermal hyperalgesia, but not mechanical allodynia. These effects were associated with decreased up‐regulation of neuronal NOS (nNOS), CGRP and c‐Fos expression in the spinal dorsal horn and/or DRG. However, i.t. administration of CTAP blocked the induction by BAM8‐22 of delayed anti‐hyperalgesia and inhibition of nNOS and CGRP expression in DRG. BAM8‐22 also increased mRNA for MORs and pro‐opiomelanocortin, along with β‐endorphin content in the lumbar spinal cord and/or DRG. MrgC receptors and nNOS were co‐localized in DRG neurons. Conclusions and Implications Activation of MrgC receptors suppressed up‐regulation of pronociceptive mediators and consequently inhibited inflammatory pain, because of the activation of up‐regulated MrgC receptors and subsequent endogenous activity at MORs. The uniquely distributed MrgC receptors could be a novel target for relieving inflammatory pain.